2015
DOI: 10.1186/s12885-015-1214-0
|View full text |Cite
|
Sign up to set email alerts
|

Low mir-372 expression correlates with poor prognosis and tumor metastasis in hepatocellular carcinoma

Abstract: BackgroundRecent studies have shown that miR-372 plays important roles in hepatocellular carcinoma (HCC) progression. However, results have been conflicting regarding its expression levels and role in HCC.MethodsRT-PCR and in situ hybridization was used to evaluate miR-372 expression in HCC tissues and cell lines. The methylation status of neighboring CpG islands upstream of the miR-372 promoter was analyzed by methylation-specific PCR (MSP). Transfection of miR-372 mimic into HCC cell lines was used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…It was also demonstrated that the miR-520/373 family has a tumor-suppressive role attributed to inhibition of the NFkB and TGFb signaling pathways (30). Furthermore, low miR-372 expression was correlated with poor prognosis and tumor metastasis in HCC (42). Moreover, the miRNA family was also shown to be a tumor suppressor gene in cervical carcinoma (43), endometrial adenocarcinoma (44) and ovarian carcinoma (45).…”
Section: Discussionmentioning
confidence: 97%
“…It was also demonstrated that the miR-520/373 family has a tumor-suppressive role attributed to inhibition of the NFkB and TGFb signaling pathways (30). Furthermore, low miR-372 expression was correlated with poor prognosis and tumor metastasis in HCC (42). Moreover, the miRNA family was also shown to be a tumor suppressor gene in cervical carcinoma (43), endometrial adenocarcinoma (44) and ovarian carcinoma (45).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we selected miR-372 because of its wide range of functional regulation in many types of human cancers (Cho et al, 2009;Lai et al, 2012;Gu et al, 2013;Wu et al, 2015). In this study, 20 pairs of serum samples were collected from patients with PCa and healthy control subjects for further confirming the pattern of expression of miR-372 in PCa.…”
Section: Mirna-372 Is Downregulated In Pcamentioning
confidence: 93%
“…HBx from HBV seems in charge of HULC upregulation and HULC silencing blocks HBx protein-mediated enhanced cell proliferation (Du et al, 2012; Wang et al, 2010). Interestingly, HULC sequesters miR-372, involved in regulation of cell cycle, apoptosis, invasion, and proliferation in many types of human cancers (Wu et al, 2015). …”
Section: Viruses and Lncrnasmentioning
confidence: 99%